Eleven days in hell : the 1974 Carrasco prison siege in Huntsville, Texas - Harper, William T., 1929- (Crime and criminal justice series, 2004)
From one o'clock on the afternoon of July 24, 1974, until shortly before ten o'clock the night of August 3, eleven days later, one of the longest hostage-taking sieges in the history of the United States took place in Texas' Huntsville State Prison.